2005
DOI: 10.1161/01.str.0000166182.50840.31
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in South West Nigeria

Abstract: Background and Purpose-Stroke is a significant economic, social, and medical problem worldwide. This retrospective follow-up study aimed to review the pattern, types, and case fatality of stroke in Nigeria. Methods-Records of all stroke patients admitted into Ogun State University Teaching Hospital (OSUTH), Sagamu, from December 1993 to November 2003 were reviewed. Patients were classified into hemorrhage or infarct using the World Health Organization criteria. Information was obtained as to the time of death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
109
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 11 publications
15
109
5
1
Order By: Relevance
“…Available hospital based studies in Nigeria suggest there are rising rates of stroke in the country [154] . Available data, at least from hospital based studies, show that stroke accounts for 0.23%-4.0% of all hospital admissions, 0.5%-45% neurological admissions and 5%-17% of deaths on medical wards.…”
Section: Hypertension As a Major Risk Factor For Stroke In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…Available hospital based studies in Nigeria suggest there are rising rates of stroke in the country [154] . Available data, at least from hospital based studies, show that stroke accounts for 0.23%-4.0% of all hospital admissions, 0.5%-45% neurological admissions and 5%-17% of deaths on medical wards.…”
Section: Hypertension As a Major Risk Factor For Stroke In Nigeriamentioning
confidence: 99%
“…It is the commonest cause of neurological admission in Lagos, the largest city and the commercial nerve centre of Nigeria. Cerebral infarction, intracerebral hemorrhage and subarachnoid haemorrhage, respectively, are responsible for 64%, 19% and 6% of strokes in the country [154] . In a community based study in Lagos [155] , stroke prevalence was estimated as 1.14 per 1000 (1.51/1000 in men, 0.69/1000 in women and 24.1/1000 in those older than 65 years.…”
Section: Hypertension As a Major Risk Factor For Stroke In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…In their seperate studies, Ogun (2005) 27 and Umuerri (2013), 28 found that Cardiovascular complications of DM such as stroke, and peripheral disease occured in 11% and 37% respectively of persons with DM respectively in hospital settings in Nigeria. However, 2.1% of cases of heart failure is noted to be due to DM.…”
Section: 26 22mentioning
confidence: 99%
“…Some studies have found haemorrhagic stroke to be commoner in adults with sickle cell disease as a result of the development of moyamoya disease [33,34] which results from the formation of poorly endothelialised vessels following vascular occlusion. In most studies on the pattern of stroke in Nigeria, ischaemic stroke has always been the more common [35][36][37][38] except in a few cases in urban centres [39] in one of which Ogun, et al used the WHO criteria to classify the stroke types. The significant difference between the two groups in this study in terms of the pathologic stroke types is likely to be due to the presence of sickle cell trait in line with the observation of Ajayi, et al [4] in their study that the risk of haemorrhagic stroke was 10 times that of ischaemic stroke in sickle cell patients.…”
Section: Relationship Between Sickle Cell Trait and Stroke Severity Amentioning
confidence: 99%